(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The article emphasizes that the experience of public speaking of the future teacher is a necessary condition for his pedagogical activity. An overview of the fundamental works of domestic and foreign studies on the topic under study is given. Their scientific contribution to pandemic pedagogy and the problems of researching the practice of personal growth, tools, means, the formation of the experience of public speaking of the future teacher, which are supplemented in the article with audience management techniques, generalization of the experience of public speaking of future teachers; materials, research methods (theoretical analysis, observation, analysis of the experience of the authors of the article) are described. The results reveal the basic principles of rhetoric on which the success of public speaking is based. Also, it highlighted the ways in which the speakers managed to establish contact with the audience and attract attention during the speech.